The Triage of Injured Patients: Mechanism of Injury, Regardless of Injury Severity, Determines Hospital Destination. Issue 4 (April 2016) - Staudenmayer, Kristan; Wang, N. Ewen; Weiser, Thomas G.; Maggio, Paul; Mackersie, Robert C.; Spain, David; Hsia, Renee Y.
The target rate for trauma undertriage is <5 per cent, but rates are as high as 30 to 40 per cent in many trauma systems. Wehypothesized that high undertriage rates were duetothe tendencyto undertriage injured elderly patients and a growing elderly population. We conducted a retrospective analysis of all hospital visits in California using the Office of Statewide Health Planning and Development Database over a 5-year period. All hospital admissions and emergency department visits associated with injury were longitudinally linked. The primary outcome was triage pattern. Triage patterns were stratified across three dimensions: age, mechanism of injury, and access to care. A total of 60, 182 severely injured patients were included in the analysis. Fall-related injuries were frequently undertriaged compared with injuries from motor vehicle collisions (MVCs) and penetrating trauma (52% vs 12% and 10%, respectively). This pattern was true for all age groups. Conversely, MVCs and penetrating traumas were associated with high rates of overtriage (>70% for both). In conclusion, in contrast to our hypothesis, we found that triage is largely determined by mechanism of injury regardless of injury severity. High rates of undertriage are largely due to the undertriage of fall-related injuries, which occurs in both younger and older adults. Patients injured after MVCs and penetrating trauma victims are brought to trauma centers regardless of injury severity, resulting in high rates of overtriage. These findings suggest an opportunity to improve trauma system performance.